Punch Grafting In Chronic Stable Vitiligo : A Preliminary Report - Sirka C. S; Thappa D. M; Agrawal K (Wolters Kluwer Medknow Publications, 1997)
Eleven patients of stable vitiligo (7 segmental, 2 focal, 2 contact depigmentation) having localized lesions were treated with autologous punch skin grafts. The cosmetic improvement at 5th month was good in 3, fair in 7 and poor in 1. However, at 7th month the improvement was excellent in 4, good in 6 and poor in 1. Complications in the form of variegated colour â€" 9 patients, cobblestoning â€" 8 patients, depigmentation â€"1 patient and graft loss in 1 patient were noted in this study. The role of adjuvant therapy (topical steroid and topical psoralen) is highlighted.